Cognitive Demands Associated with the Use of Cognitive Reappraisal to Regulate Positive and Negative Emotion - Hefyan, Mervett (Tufts Archival Research Center, 2005)
As cognitive reappraisal is an effortful process, differences in cognitive demand could help to explain how and when the emotion regulation strategy is executed, such as among individuals with fewer cognitive resources. While some studies have already suggested that increasing and decreasing one's responses to emotional information are more effortful goals than the passive viewing of emotional information, these studies have not looked across multiple regulation and valence conditions, failing to reflect the variety of emotional situations we face in daily life. In the present study, pupil diameter was measured as an index of cognitive demand as 63 undergraduate students increased, decreased, and maintained their emotional response towards pleasant and unpleasant stimuli. We hypothesized that (1) increasing and decreasing one's emotional response would result in significantly greater pupil dilation than passive viewing, and (2) increasing one's emotional response would result in greater pupil dilation than decreasing. Although the hypotheses were not supported by the data, the analysis showed that the maintain instruction elicited greater pupil dilation than the decrease instruction during the instruction portion of the trial. This result might suggest that cognitive reappraisal, if anything, is less cognitively demanding than passively viewing emotional stimuli. More likely, however, is that this result is due to a limitation of the study design.